ERADICATING MALARIA AND SIMULATING THE CORRECT USE OF MOSQUITO NET FOR STUDENTS IN BIAK DORMITORY JAYAPURA CITY - Ayomi, Mina B.; Bouway, Dolfinus Y.; Pariaribo, Kostantina; Tukan, Dessy O.; Rumwaropen, Fancika N.; Tabuni, Peni; Wenda, Sutana (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: Malaria is a disease caused by the Plasmodium parasite. This disease is transmitted through the bite of a female Anopheles mosquito which is infected with this parasite and attacks all humans. How to prevent it by avoiding or reducing malaria mosquito bites is not doing activities outside the house at night, sleeping under a mosquito net, smearing the body with anti-mosquito bite material. , installing screens on ventilation, cleaning mosquito breeding areas, clearing bushes or shady trees around the house or by doing 3M (burying, draining and covering). The aim of this service is to increase Malaria knowledge among students and train students on how to use mosquito nets correctly at the Biak Dormitory, Jayapura City. Methods: Malaria eradication action methods, namely lectures conducted by providing information about the correct use of mosquito nets and simulations, namely practicing how to use and care for mosquito nets correctly, the activity was carried out at the Biak Dormitory located in Padang Bulan, Jayapura City on November 29 2023. There were 13 participants involved in this activity who had the status of active students at several universities. high in Jayapura City. Results: The results of the action to eradicate Malaria with the correct use of mosquito nets before giving students knowledge material were still lacking at 38.4% or there were still 5 students. After receiving the material, student knowledge increased 100% or all students already had correct knowledge about Malaria. Conclusion: The real action carried out by students at the Biak Dormitory is an effort to eradicate Malaria at the right target, because students can disseminate information about malaria prevention locally and can help with the Malaria Elimination program by 2030.